Digilogue : How to Win the Digital Minds and Analogue Hearts of Tomorrow's Customer. - Sorman-Nilsson, Anders (Wiley, 2013)
How to leverage the enduring human need for analogue experiences to attract and retain more customers in a digital world. Anything that can be digitised will be digitised. But can the digital-connect ever really replace the personal touch? Is word-of-mouse always more effective than word-of-mouth? And what of customers' enduring need for analogue experiences (think analogue watches, paperback books and multiplex movie theatres, for example). In your rush to embrace your customers' digital mind are you ignoring an equally valuable asset: their analogue heart? Better yet, h.